On decay constants and orbital distance to the Sun—part III: beta plus and electron capture decay. (28th November 2016) - Pommé, S; Stroh, H; Paepen, J; Van Ammel, R; Marouli, M; Altzitzoglou, T; Hult, M; Kossert, K; Nähle, O; Schrader, H; Juget, F; Bailat, C; et al.
Abstract: The hypothesis that seasonal changes in proximity to the Sun cause variation of decay constants at permille level has been tested for radionuclides disintegrating through electron capture and beta plus decay. Activity measurements of 22 Na, 54 Mn, 55 Fe, 57 Co, 65 Zn, 82+85 Sr, 90 Sr, 109 Cd, 124 Sb, 133 Ba, 152 Eu, and 207 Bi sources were repeated over periods from 200 d up to more than four decades at 14 laboratories across the globe. Residuals from the exponential nuclear decay curves were inspected for annual oscillations. Systematic deviations from a purely exponential decay curve differ from one data set to another and appear attributable to instabilities in the instrumentation and measurement conditions. Oscillations in phase with Earth's orbital distance to the sun could not be observed within 10 −4 –10 −5 range precision. The most stable activity measurements of β + and EC decaying sources set an upper limit of 0.006% or less to the amplitude of annual oscillations in the decay rate. There are no apparent indications for systematic oscillations at a level of weeks or months.